2004
DOI: 10.1620/tjem.203.133
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Invasive Aspergillosis Originating in the Sphenoid Sinus: A Successful Treatment with High-Dose Itraconazole in Three Cases

Abstract: We report three cases of intracranial aspergillosis originating in the sphenoid sinus in immunocompetent patients. The patients presented with an orbital apex syndrome in that a unilateral loss of vision and cranial nerve III palsy were seen in all cases and a contralateral involvement was also seen in one case. Despite the initial treatment with a conventional dose of itraconazole (ITCZ, 200 mg/day), the neurological deficits failed to improve and the granulomatous inflammation was not suppressed. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Despite a long course of treatment the compliance of the patients was good with itraconazole. We used conventional doses of itraconazole (4-6 mg kg body weight per day).Yamanoi et al [14], has used high dose of itraconazole (16-24 mg/kg) in his study with few side effects. Due to erratic bioavailability of itraconazole serum drug concentration monitoring has been advised.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a long course of treatment the compliance of the patients was good with itraconazole. We used conventional doses of itraconazole (4-6 mg kg body weight per day).Yamanoi et al [14], has used high dose of itraconazole (16-24 mg/kg) in his study with few side effects. Due to erratic bioavailability of itraconazole serum drug concentration monitoring has been advised.…”
Section: Discussionmentioning
confidence: 99%
“…Severe orbital apex syndrome with EMD and reduced vision caused by aspergillosis might need emergency treatments of antifungal therapy, steroid, and surgical decompression (Yamanoi et al 2004). On the other hand, a spontaneous orbital hemorrhage is a rare condition that causes acute ocular pain, exophthalmos, EMD, diplopia, and reduced vision (Shimura et al 1992).…”
Section: © 2005 Tohoku University Medical Pressmentioning
confidence: 99%
“…Furthermore, a series of three cases of chronic invasive aspergillosis of the sinus showed that high-dose ITCZ therapy is effective [8]. These three cases were treated only with high-dose ITCZ capsules.…”
Section: Discussionmentioning
confidence: 99%